MRI Heralds Secondary Nigral Lesion after Brain Ischemia in Mice: A Secondary Time Window for Neuroprotection. Issue 12 (December 2015) - Prinz, Vincent; Hetzer, Anna-Maria; Müller, Susanne; Balkaya, Mustafa; Leithner, Christoph; Kronenberg, Golo; Endres, Matthias
Cerebral ischemia in the territory of the middle cerebral artery (MCA) can induce delayed neuronal cell death in the ipsilateral substantia nigra (SN) remote from the primary ischemic lesion. This exofocal postischemic neuronal degeneration (EPND) may worsen stroke outcomes. However, the mechanisms leading to EPND are poorly understood. Here, we studied the time course of EPND via sequential magnetic resonance imaging (MRI) and immunohistochemistry for up to 28 days after 30 minutes occlusion of the MCA (MCAo) and reperfusion in the mouse. Furthermore, the effects of delayed treatment with FK506 and MK-801 on the development of EPND were investigated. Secondary neuronal degeneration in the SN occurred within the first week after MCAo and was characterized by a marked neuronal cell loss on histology. Sequential neuroimaging examinations revealed transient MRI changes, which were detectable as early as day 4 after MCAo and thus heralding histologic evidence of EPND. Treatment with MK-801, an established anti-excitotoxic agent, conferred protection against EPND even when initiated days after the initial ischemic event, which was not evident with FK506. Our findings define a secondary time window for delayed neuroprotection after stroke, which may provide a promising target for the development of novel therapies.